Brief and long maternal separation in C57Bl6J mice: behavioral consequences for the dam and the offspring - Rombaut, Cynthia; Roura-Martinez, David; Lepolard, Catherine; Gascon, Eduardo (Frontiers in Behavioral Neuroscience, 2023)
Introduction Animal models, especially rodents, have become instrumental to experimentally investigate the effects of an adverse post-natal environment on the developing brain. For this purpose, maternal separation (MS) paradigms have been widely used in the last decades. Nonetheless, how MS affects maternal behavior and, ultimately, the offspring depend on multiple variables. Methods To gain further insights into the consequences of MS, we decided to thoroughly measure and compare the effects of short (15 min, 3 times/day) vs long (3h, 1 time/day) separation on multiple maternally-associated behaviors and across the entire post-natal period. Results Compared to unhandled control litters, our results confirmed previous studies and indicated that SMS enhanced the time and variety of maternal care whereas LMS resulted in poor caregiving. We also showed that SMS-accrued caregiving persisted during the whole post-natal period. In contrast, LMS effects on maternal behavior were restricted to the early life (P2-P10). Finally, we also analyzed the behavioral consequences of these different rearing social environments on the offspring. Our findings show that MS has profound effects in social tasks. Of utmost importance, we showed that affiliative touch, a type of prosocial behavior that provides comfort to others, is particularly sensitive to the modification of maternal caregiving. Discussion Our results provide further support to the contention that interactions during the early post-natal period critically contribute to emotional processing and brain co-construction.